2013
DOI: 10.5007/2175-7925.2013v26n2p19
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura diamétrica da vegetação arbustivo-arbórea no entorno de nascentes da bacia hidrográfica do rio Piauitinga, Salgado – SE, Brasil

Abstract: ResumoEste estudo foi realizado com o propósito de analisar a estrutura diamétrica da vegetação ciliar em nascentes da bacia hidrográfica do rio Piauitinga, localizadas no município de Salgado-SE. Foram analisadas 14 nascentes, mediante classificação quanto ao estado de conservação e ao tipo de reservatório, sendo divididas em 4 categorias: 1 preservada pontual (PrP), 1 perturbada pontual (PP), 6 degradadas pontuais (DP) e 6 degradadas difusas (DD). O levantamento foi realizado por meio de censo populacional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
2
0
2
Order By: Relevance
“…At least two of the four families with the highest specific richness in this study were also predominant, sometimes reversing the order of importance, in phytosociological studies carried out in other fragments or ecosystems associated with the Sergipe Forest Atlantic (e.g., Dantas et al 2010;Oliveira et al 2013) and in Northeastern Brazil (e.g., Tavares et al 2000;Andrade and Rodal 2004;Brandão et al 2009).…”
Section: Discussionsupporting
confidence: 57%
“…At least two of the four families with the highest specific richness in this study were also predominant, sometimes reversing the order of importance, in phytosociological studies carried out in other fragments or ecosystems associated with the Sergipe Forest Atlantic (e.g., Dantas et al 2010;Oliveira et al 2013) and in Northeastern Brazil (e.g., Tavares et al 2000;Andrade and Rodal 2004;Brandão et al 2009).…”
Section: Discussionsupporting
confidence: 57%
“…Estas famílias também se destacam no estudo de Arantes et al (2012), em reflorestamento (80 meses) e em fragmento preservado. Oliveira et al (2013a) na avaliação da regeneração natural em nascentes, na mesma região do presente estudo, destacam que a família Myrtaceae também apresenta maior número de espécies, onde demonstram ser comum o alto número de espécies desta família na região. Maria-RS, v.7, e02, 2019 Tabela 2 -Famílias, espécies e grupos ecológicos em floresta em estágio avançado de sucessão, São Cristóvão, SE.…”
Section: Resultsunclassified
“…The distribution of individuals per diameter class in both evaluation periods follows the inverted "J" pattern, considered characteristic of native forests (Oliveira et al, 2013). Although a large number of small and thin individuals may indicate the occurrence of past disturbances (Nunes et al, 2003), the observed tendency in the growth of the individuals' diameter in intermediate classes in t 1 may indicate successional evolution (Chagas et al, 2001, Paula et al, 2002.…”
Section: Discussionmentioning
confidence: 98%